2021
DOI: 10.48550/arxiv.2104.11055
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Many-body localization transition from flatband fine-tuning

Carlo Danieli,
Alexei Andreanov,
Sergej Flach

Abstract: Translationally invariant flatband Hamiltonians with interactions lead to a many-body localization transition. Our models are obtained from single particle lattices hosting a mix of flat and dispersive bands, and equipped with fine-tuned two-body interactions. Fine-tuning of the interaction results in an extensive set of local conserved charges and a fragmentation of the Hilbert space into irreducible sectors. In each sector, the conserved charges originate from the flatband and act as an effective disorder in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Flatband networks are increasingly permeating the quantum many-body field. Indeed, single-particle CLS have been extended to many-body CLS [29][30][31], while quantum scars [32][33][34] and MBL-like dynamics [35][36][37] have been reported very recently in flatband lattices. But more importantly, it has been shown that fine-tuning of the interaction in ABF networks induces an extensive set of local constraints which completely suppress charge transport in any spatial dimension -a phenomenon called many-body flatband localization (MBFBL) [38][39][40].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Flatband networks are increasingly permeating the quantum many-body field. Indeed, single-particle CLS have been extended to many-body CLS [29][30][31], while quantum scars [32][33][34] and MBL-like dynamics [35][36][37] have been reported very recently in flatband lattices. But more importantly, it has been shown that fine-tuning of the interaction in ABF networks induces an extensive set of local constraints which completely suppress charge transport in any spatial dimension -a phenomenon called many-body flatband localization (MBFBL) [38][39][40].…”
mentioning
confidence: 99%
“…These results and open quests emphasize MBFBL networks as experimentally realizable [64][65][66] valid platforms to explore novel phenomena in quantum systems -highlighting jointly with Refs. [29][30][31][32][33][34][35][36][37][38][39][40] the progressively growing relevance of flatbands in the realm of many-body physics.…”
mentioning
confidence: 99%